(untitled) (Research, Society and Development, 2022)
Objective: to analyze the benefits of aesthetic procedures that delay skin aging on women’s self-esteem. Methods: This is a descriptive, exploratory research, with a qualitative approach, carried out in an Aesthetics Clinic located in the municipality of Vitória da Conquista. Participants were 15 women aged over 25 years, who have been performing procedures at the clinic for at least 6 months. An interview was conducted based on a semi-structured script and the data were submitted to the researcher’s analysis. Results: The results showed that many women feel the need to undergo aesthetic procedures, which directly affect their self-esteem. Final considerations: It is concluded that there are numerous benefits of aesthetic procedures, which will directly influence women’s self-esteem.